Pola Komunikasi Mahasiswa dan Orang Tua Studi Deskriptif Kualitatif Mahasiswa Universitas Pancasakti Makassar - Hermin Andi Magga; Muhtazib Muhtazib (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This research aims to find out how the pattern of long-distance communication between students of Pancasakti University Makassar and parents for students who come from Manggarai East Nusa Tenggara (NTT). The research method used is qualitative, with the selection of informants by sampling by taking 20 student informants. The background of the author took this title because in general, children and parents are in close contact and often communicate face-to-face because they live in one house. But it is different with parents and children who do not live in the same house or live far apart due to differences in distance and place. Communication is carried out using media such as gadgets (cellphones) not communicating face-to-face. This long-distance communication creates a problem, namely that the communication that is established becomes effective or no longer effective because the communication between parents and children becomes an emotional relationship that is no longer intertwined.